IFITM3 Rs12252-C Variant Increases Potential Risk for Severe Influenza Virus Infection in Chinese Population. - Pan, Y; Yang, P; Dong, T; Zhang, Y; Shi, W; Peng, X; Cui, S; Zhang, D; Lu, G; Liu, Y; Wu, S; Wang, Q (Frontiers Media, 2017)
Background: Interferon Inducible Transmembrane 3 (IFITM3) is a key factor in interferon pathway and it involves host's immune response against multiple viruses. IFITM3 rs12252-C was associated with severe influenza virus infection in several studies, however whether this association is universal to all types of influenza virus or diverse ethnic populations remain controversial. Method: A case-control genetic association study was performed from September 2013 to April 2014 and September 2014 to April 2015. All samples were tested for influenza using RT-PCR, and genotyped by High Resolution Melting assay. Results: A total of 65 healthy people, 165 mild influenza-like illness (ILI) cases and 315 severe acute respiratory infection (SARI) cases were enrolled in this study. The frequency of CC genotype was much higher in SARI cases with IVI than that in ILI cases with IVI (61.59 vs. 27.16%), leading a 4.67-fold greater risk for severe IVI than other two genotypes. Moreover, the risk of IFITM3 rs12252-C variant for severe IVI was specific for both influenza A and influenza B. Conclusion: IFITM3 rs12252 CC genotype was associated with severity rather than susceptibility of IVI in Chinese population, and this strong effect was observed in all subtypes of seasonal influenza infection.